Implementasi Peraturan Daerah Kabupaten Indragiri Hilir Nomor 2 Tahun 2021 Tentang Perlindungan Lahan Pertanian Pangan Berkelanjutan : Studi Kasus Kecamatan Tembilahan Hulu - Tia Suherianti; Sujianto Sujianto (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The policy of protecting sustainable food agricultural land (LP2B) is to be able to protect and defend agricultural land areas. A total of seven sub-districts out of twenty sub-districts in Indragiri Hilir Regency have been designated as Sustainable Food Agricultural Land (LP2B). This study aims to describe the implementation of Regional Regulation Number 2 of 2021 concerning the Protection of Sustainable Food Agricultural Land (LP2B) and the constraint factors faced. The research method used is qualitative research with a case study approach using theory from Smith which has 4 variables that affect policy success, namely Idealized Policys, Target Groups, Implementation Organization, Environmental Factors. The results of the study found that the implementation of Regional Regulation Number 2 of 2021 concerning the Protection of Sustainable Food Agricultural Land (LP2B) has not been optimal due to the findings of obstacles faced in its implementation. The suggestion from this study is that implementors and target groups are expected to be able to be more optimal in protecting sustainable food agricultural land amid the rampant land conversion carried out.